Peach Rust - Courtney Ligon; Mercy Olmstead; Philip Harmon (EDIS)
Peach rust is a fungal disease that affect the leaves and, less commonly, twigs and fruit of peach trees. The fungus that causes peach rust thrives in Florida’s humid climate and may cause significant economic losses in severely affected orchards. This 5-page fact sheet details peach rust symptoms, disease cycle, and management, including fungicide treatments. Written by Courtney Ligon, Mercy Olmstead, and Phillip Harmon, and published by the UF Department of Horticultural Sciences, June 2015.